The Cooperation between Teachers and Parents to Develop Learning Ability for Primary School Students at Home during the Covid-19 Pandemic - Wibowo, Dodiet Enggar; Mahmudi, Ali; Retnawati, Heri (Journal of Education Research and Evaluation, 2021)
The objective of this study is to develop the learning abilities of elementary school students during the Covid-19 pandemic by establishing cooperative relationships between teachers and parents. The research design are exploratory case studies, data collection instruments with semi-structured interview methods, and Focused group Discussion (FGD). The results of the research on the impact of Covid-19 showed that online learning are not effective compared to face-to-face learning in the classroom, the obstacles in online learning including unstable networks, and lack of parents’ ability to help explaining the material provided by the teacher. Good cooperation and communication between parents and teachers are the solution to optimize study from home.